Observations on the use of a pain numbing device for repetitive percutaneous sampling in sheep. Issue 10 (27th June 2021) - Munn, R; Woodward, A; Beths, T; Whittem, T
Abstract : Aims: To evaluate the success of a commercially available analgesic device (CoolSense; Coolsense Ltd, Tel Aviv, Israel) in ameliorating pain while sampling from subcutaneous tissue cages in sheep. Methods: The CoolSense device was used as part of a major parent study involving repetitive percutaneous sampling of subcutaneous tissue cages in seven sheep. Sampling was performed by passing a hypodermic needle through the skin and withdrawing fluid from the tissue cage. Each sheep had 10 tissue cages that were individually sampled 14 times over 74 h. The device was placed on the skin of the sampling site immediately before sampling cooling and numbing the skin. The reaction of the sheep was observed by the operators, flinching or jumping as the needle was passed through the skin was deemed to be a failure. We recorded the success or failure of the device for each needle stick. This was opportunistic data collection as part of a pharmacokinetic trial, therefore no controls were included. Results: A total of 1655 observations were recorded and then analysed using a generalised linear mixed model. Overall, 1380 of 1655 (83.4%) observations were recorded as successfully providing analgesia. Marked inter‐occasion variability was noted with success ranging from 61.42% to 92.86% across sheep:period (approximately 140 observations each). As no controls were available, the effect of treatment could not be evaluated. Conclusions and clinical relevance: The CoolSense device is a viable option for veterinary research and clinical applications.